Contemporary Developments and Perspectives in International Health Security Volume 1 - Stawicki, Stanislaw P.; Firstenberg, Michael S.; Galwankar, Sagar C.; Izurieta, Ricardo; Papadimos, Thomas (IntechOpen, 2021)
International health security (IHS) is a broad and highly heterogeneous area. Within this general context, IHS encompasses subdomains that potentially influence (and more specifically endanger) the well-being and wellness of humans. The general umbrella of IHS includes, but is not limited to, natural disasters, emerging infectious diseases (EID) and pandemics, rapid urbanization, social determinants of health, population growth, systemic racism and discrimination, environmental matters, civilian violence and warfare, various forms of terrorism, misuse of antibiotics, and the misuse of social media. The need for this expanded definition of health security stems from the realization that topics such as EID; food, water, and pharmaceutical supply chain safety; medical and health information cybersecurity; and bioterrorism, although important within the overall realm of health security, are not only able to actively modulate the wellness and health of human populations, but also tend to do so in a synergistic fashion. This inaugural tome of a multi-volume collection, Contemporary Developments and Perspectives in International Health Security, introduces many of the topics directly relevant to modern IHS theory and practice. This first volume provides a solid foundation for future installments of this important and relevant book series.